Latest Development on Sustainability Programme Initiatives in Malaysian Healthcare Facility Management - Muhammad Syukri Imran, Abdullah; Noor Muhammad, Abdul Rahman; Tauran Zaidi, Ahmad Zaidi; Khairul Azmy, Kamaluddin (2019)
Government healthcare facility management (FM) in Malaysia has gone a long way since it was privatised in the 90s. The implementation of sustainability program in healthcare FM practice have managed to save the Federal Government about RM 60 million up to 2018 (2015/16 baseline) or about 106 ktonne carbon offset. Every government hospitals have either achieved 1 star or 2 star certification under the Energy Management Gold Standard (EMGS). Several hospitals and clinics have also been selected for the green hospital and clinic pilot projects under the MOH green initiative for smart healthcare facilities. Various energy projects have been implemented in public hospitals some through Energy Performance Contracting (EPC). The Malaysian Certified Healthcare Facility Manager (CHFM) is a formal education programme that has been developed and offered for the healthcare FM locally and internationally. The aim of this paper is to review the advancement of the FM implementation in public healthcare sector particularly on how sustainability program is being practice within the FM itself.